Augmented reality applications for robots in industry - Muhammad Hilmi Abideen (2018)
This paper will be investigating the possibility of using Augmented Reality (AR) apps in mobile devices, such as tablets and laptops, to allow simpler programming and control of a simple robot arm, as well as the possible future applications of such technology in automation and process technology. A Microsoft Surface Pro was used as the AR device, controlling a MeArm robotic arm wirelessly via an Wemos D1 Mini IOT Board. The accuracy of motion of the arm was tested and the application of AR capabilities was evaluated. It was found that the point and click method used was able to achieve the desired goal within the limitations of the experiment. However, additional functions need to be integrated if an AR app is to be used in an industrial setting. These additional functions may include, but are not limited to, complex AR techniques such as obstruction detection, and use of virtual guides, previews and models. These additional functions will allow such an app to control robot arm capabilities outside the scope of the arm used in this experiment, such as force and speed control, tool changes and a higher number of degrees of freedom.